Development dimension of FDI : policy and rule-making perspectives : proceedings... - Zampetti, Americo Beviglia (UN New YorkUS, 2003)
Discusses the role of FDI-related host country policies in encouraging synergies between inward FDI and the domestic enterprise sector. Looks at the potential role of home country policy measures in this context. Addresses the role of safeguards and the right of host governments to regulate.